The premonition at Withers Farm [large type] - Wright, Jaime Jo (Thorndike Press large print Christian fiction series., 2023)
"In 1910, rural healer Perliett VanHilton is targeted by a superstitious killer and must rely on the local doctor and an intriguing newcomer for help. Over a century later, Molly Wasziak is pulled into a web of deception surrounding an old farmhouse. Will these women's voices be heard, or will time silence their truths forever?"--